Investigating The Self-Esteem of Elemantary Boarding Scholls' Students - Azmi İlbay; İsmail Ay; İsmail Seçer; Muhammet Çiftçi (Sakarya University, 2013)
In this study, the second-tier regional boarding primary schools, students are receiving education and self-esteem levels of age, gender, type of study, academic achievement and significant differences according to the variables whether or not to take disciplinary action were investigated. 2010-2011 academic research in the regional boarding primary schools are receiving education in Erzurum, which was carried out on 428 students. Piers and Harris to collect data from the study (1964), developed by the self-esteem scale has been used in children. T-test analysis of the data, one-way analysis of variance and LSD post hoc test technique was used. Research students' self-esteem levels as a result of the type of learning, academic achievement and significant differences were identified according to their discipline.